THE RELATIONSHIP OF BMI WITH THE MENSTRUAL CYCLE IN KRIDA WACANA CHRISTIAN UNIVERSITY STUDENTS FOR THE PERIOD OF MARCH – JULY 2022 - Alice Orine Ximenes de Jesus Sarmento; Irene Maria Elena; Luciana Budiati Sutanto; Gracia J M T Winaktu (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Body mass index (BMI) data from RISKESDAS shows that many women of childbearing age in Indonesia experience BMI problems and there are also several studies showing a significant relationship between BMI and the menstrual cycle. FKIK UKRIDA students with analytic research type and crosssectional design. From the data collection, there were 86 subjects from affordable populations who had been filtered according to the inclusion and exclusion criteria and the distribution of BMI data with menstrual cycles, namely there were no thin and normal BMI subjects who had oligomenorrhea, while the fat ones who experienced oligomenorrhea were 1.2%, for thin BMI with normal menstrual cycles there were 16.3%, normal BMI with normal menstrual cycles were 52.3%, and obese BMI with normal menstrual cycles were 24.4%. Meanwhile, thin BMI with polymenorrhea was 1.2% and there were no normal BMI subjects who had polymenorrhea, but in obese BMI with polymenorrhea there was 4.7%, in data analysis using Fisher's test there was P value = 0.010. Conclusion: there is a significant relationship between BMI and the menstrual cycle of FKIK UKRIDA students with P value = 0.010.